BLIND PEOPLE’S EMPOWERMENT THROUGH EDUCATION AND TRAINING (CASE STUDIES IN THE MITRA NETRA FOUNDATION AND PSBN MIYAT TAN) - Ray Septianis Kartika (Widyariset, 2011)
People with visual impairment is one who just had a vision defect, not a personality flaw nor defect in the will. Even reversed their eyesight defects, many of the potencies latent are difficult to actualize due to a lack of accessibility that they can get. Therefore it would be wise if the government agencies / private sector are more concerned and attentive to this issue. Blind people, as part of the Indonesian people, should be brought out of poverty that shackled his life. This means that they are given the opportunity to transform themselves into better by participating in education and training, so they can become professional and reliable. Thus, their the empowermentof people with visual impairment is an effort to improve a certain dignity in order to escape limitations.